Capillary refill time vs serum lactate measurement in septic shock patients: Which is better in Emergency department? - Adhikari, Sunil (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Clinical Question: Does the use of a resuscitation strategy that targets normalization of capillary refill time compared with a strategy that targets serum lactate levels reduce mortality among patients in septic shock? Article Chosen: Glenn HernÃ¡ndez, Gustavo A. Ospina-Tascón, Lucas Petri Damiani et al. Effect of a Resuscitation Strategy Targeting Peripheral Perfusion Status vs Serum Lactate Levels on 28 Day Mortality Among Patients with Septic Shock. The ANDROMEDA-SHOCK Randomized Clinical Trial. JAMA. 2019;321(7):654-664.1 Objective: The study’s objective was to determine if a resuscitation strategy guided by peripheral perfusion using capillary refill time was superior to lactate-guided resuscitation among adults admitted to the intensive care unit with early septic shock. Conclusion: Assessing capillary refill time is an age-old easy manner to assess tissue perfusion. It is more applicable to our settings where lactate measurement may not be available in all health centres and assessing capillary refill time can guide us in resuscitation and reduce mortality together with or without serum lactate measurement.